The Molecular Evolution and Functional Divergence of Lamprey Programmed Cell Death Genes - Guan, Xin; Lu, Jiali; Sun, Feng; Li, Qingwei; Pang, Yue (Frontiers in Immunology, 2019)
The programmed cell death (PDCD) family plays a significant role in the regulation of cell survival and apoptotic cell death. However, the evolution, distribution and role of the PDCD family in lampreys have not been revealed. Thus, we identified the PDCD gene family in the lamprey genome and classified the genes into five subfamilies based on orthologs of the genes, conserved synteny, functional domains, phylogenetic tree and conserved motifs. The distribution of the lamprey PDCD family and the immune response of the PDCD family in lampreys stimulated by different pathogens were also demonstrated. In addition, we investigated the molecular function of lamprey PDCD2, PDCD5 and PDCD10. Our studies showed that the recombinant lamprey PDCD5 protein and transfection of the L-PDCD5 gene induced cell apoptosis, upregulated the expression of the associated X protein (BAX) and TP53 and downregulated the expression of B cell lymphoma 2 (BCL-2) independent of Caspase 3. In contrast, lamprey PDCD10 suppressed apoptosis in response to cis-diaminedichloro-platinum (II) stimuli. Our phylogenetic and functional data not only provide a better understanding of the evolution of lamprey PDCD genes but also reveal the conservation of PDCD genes in apoptosis. Overall, our results provide a novel perspective on lamprey immune regulation mediated by the PDCD family.